Threat to Professional Autonomy and Physicians' Intention to Use Acupuncture: A Study From Malaysia - Daher, Aqil M.; Ong, Siew Siew; Krisnan, Devanandhini (Frontiers in Public Health, 2022)
Despite its popularity, registered medical practitioners (RMP) are reluctant to use acupuncture in their practice. The aim of this study is to determine the impact of Threat to Professional Autonomy (TPA) on RMPs’ intention to use acupuncture in Malaysia. A cross sectional study was conducted using an online survey form. The survey was distributed to 250 registered medical practitioners who are affiliated with Malaysian Medical Association. The questionnaire followed a modified technology acceptance theoretical framework including the three main constructs of ease of use, usefulness and intention to use with addition of TPA as a predictor of physician intention to use acupuncture. Structural equation modelling (SEM) was utilised to test the relationship between the 4 constructs. Measurement model, discriminant validity and path analysis statistics were presented. Two hundred and seventeen returned the completed questionnaire yielding a response rate of 86.8%. In the measurement model, all items within each construct were highly correlated. The minimum average variance extracted (AVE) was 0.741. All constructs achieved a minimum of 0.896 reliability estimates. Discriminant validity was ascertained with the findings that the square root of AVE is larger than the correlation between each two constructs. TPA has a significant negative impact on ease of use (p<0.001) and perceived usefulness (p=0.002). There was no significant direct effect of TPA on intention (p= 0.0561). Fit indices showed adequate fit. In conclusion, TPA affects the intention to use acupuncture indirectly through its negative effect on perceived ease of use and perceived usefulness of acupuncture.